Faktor determinan volume pembiayaan perbankan syariah dengan pertumbuhan ekonomi sebagai variabel moderasi - Makfiroh, Laelatul; Asna Annisa, Arna (Nur Science Institute, 2022)
The study aimed to determine the effect of third-party funds, inflation, and non-performing financing on the volume of Islamic banking financing with economic growth as a moderating variable in Islamic commercial banks in Indonesia in 2016–2020. The data used is secondary data, which is processed using the moderated regression analysis method (MRA). The study results show that third-party funds, inflation, and non-performing financial variables significantly affect financing volume. Partially, third-party funds and inflation positively affect the volume of financing. Non-performing financing does not affect the volume of financing. Economic growth could moderate the effect of third-party funds on financing volume, while inflation and non-performing financing were not moderated economic growth to the financing volume.